PERANCANGAN BLUEPRINT ANTI-FRAUD PROGRAM UNTUK MEMINIMALISASI RISIKO TERJADINYA FRAUDDI CV MOGA JAYA - Juan Christanto Hendrawan; Stevanus Hadi Darmadji (Perpustakaan Universitas Surabaya, 2018)
This is a qualitative-explanatory research and is a basic research because the researcher tried to design anti-fraud program in order to help the company to minimize the risk of fraud occurring inthe short and long term. Companies used by researchers is a family business that has a medium business scale (UMKM). UMKM has a huge contribution to the overall Indonesia's GDP with a figure that reached 57% in 60% and continues to grow in the future. UMKMs also contribute to the provision of employment in Indonesia with an average employment upto 95% annually over the past five years. The average growth of UMKMs is also always positive, including the apparel industry. This good growth were not followed by any good news about the internal control of UMKM itself. Previous research suggests that internal controls built by SMEs are less effective. Another concern states that family business also has an internal control that is not very effective when compared with non-family businessbecause of lack of implementation and excessive trust. A weak internal control, regardless of the lackof scope or implementation, will make a business vulnerable to fraud with any motivation (four fraud motivations based on fraud diamonds). Therefore, it is very important for an organization to design an Anti-Fraud Program to minimize the risk of fraud, especially by eliminating the opportunity factor. The results show that the company has implemented anti-fraud programs, although it is still very limited, and desire to create an effective anti-fraud program in a short time. Therefore, researcher will try to design an effective anti-fraud blueprint program for companies, especially for the income cycle.